Investigation of Flange Local Bending Under Flexible Patch Loading - Carden, Lyle P.; Pekcan, Gokhan; Itani, Ahmad M. (Engineering Journal, 2008)
The limit state of flange local bending due to applied flexible patch loads was investigated both experimentally and analytically in this study. Analyses showed that an unstiffened beam, supporting a timber or steel post similar to those found in bridge falsework, should be designed for a combination of flange bending and post strength. A series of experiments and finite element analyses were conducted to observe and quantify this limit state and to develop predictive methods for the evaluation of joint capacity. An interaction method was introduced in which both flange bending and timber post crushing capacities are considered. An alternative method that utilizes an effective bearing area of the post was developed, yielding more accurate capacity predictions when a steel post is used. Blocking, sometimes placed between the flanges, increased the capacity of the joint region by up to 70% with a timber post; in contrast, with a steel post, blocking improved the joint capacity by less than 25%. A post eccentricity of up to 6th of the flange width resulted in a reduction of flange-timber post joint strength by 10 to 15%. The effect of a post eccentricity was negligible with a steel post. Finally, equations to calculate the ultimate load for flange local bending are presented in both LRFD and ASD formats.